KUALITAS HUBUNGAN PELAYANAN INFORMASI OBAT TERHADAP KEPUASAN PASIEN DIRUMAH SAKIT UMUM DAERAH DAYA DAN RUMAH SAKIT TK. II PELAMONIA KOTA MAKASSAR - Febriani, Rika; Emelda, Andi; Dewi Yuliana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Pharmacists play an important role in providing quality drug information to patients. Good drug information services can reflect the quality of health services and increase patient satisfaction. This study aims to measure the quality of drug information services and patient satisfaction at Daya Hospital and Pelamonia Tk. II Hospital, Makassar, and to determine the relationship between the two. This study is descriptive with cross-sectional approach, involving 318 respondents in each hospital. The results showed that the quality of drug information service at RSUD Daya was good (57.23%) and at RS Tk. II Pelamonia was also good (57.54%). Patient satisfaction at RSUD Daya, using Importance Performance Analysis (IPA) method, on tangible dimension (71.42%), reliability (73.21%), responsiveness (73.38%), assurance (75.55%), and empathy (76.29%). At Tk. II Pelamonia Hospital, patient satisfaction in the dimensions of tangible (66.47%), reliability (70.77%), responsiveness (69.55%), assurance (73.74%), and empathy (72.28%). The chi-square statistical test shows a significant relationship between the quality of drug information services and patient satisfaction with a Sig value. 0.000 ≤ 0.05 in both hospitals.